Comparative study of photovoltaic thermal (PVT) integrated thermoelectric cooler (TEC) fluid collectors. (April 2019) - Dimri, Neha; Tiwari, Arvind; Tiwari, G.N.
Abstract: In this research, photovoltaic thermal integrated thermoelectric cooler (PVT-TEC) collector has been analyzed, considering three different types of PV modules, namely opaque, semitransparent and Aluminium base. The analysis is based on two models namely, thermal model and artificial neural network (ANN) model. The advantage of ANN model is that it does not require several parameters and complex calculations, unlike thermal model. The performance of opaque PVT-TEC collector [Case 1] has been studied by considering air [Case 1a] and water [Case 1b] as working fluids. The overall electrical efficiency and thermal efficiency of [Case 1b] is greater than [Case 1a] by 1.9–2.8% and 20.8–21.8%, respectively. Also, the impact of base cover material of PV module has been discussed by evaluating and comparing the performances of [Case 1b] opaque PVT-TEC water collector, [Case 2] semitransparent PVT-TEC water collector and [Case 3] Aluminium base PVT-TEC water collector. The results demonstrate that the daily overall electrical energy gain, daily rate of thermal energy gain and daily overall exergy gain is the highest for [Case 3] Aluminium base PVT-TEC water collector. Further, the results calculated from thermal model have been compared with ANN model and a fair agreement has been achieved. Highlights: PVT-TEC fluid collectors have been examined based on thermal model and ANN model. The electrical and thermal efficiencies of opaque PVT-TEC air and water collectors have been compared. The effect of base cover material of PV module has been discussed. The results obtained from ANN model have been compared with thermal model.